Exploring the impact of culture on consumers’ animal welfare perceptions and the attitude-behaviour gap. A cross-cultural study of postgraduate students from the UK and Mexico. - Chissell, Alice (2018)
Animal welfare is an ethical issue which is becoming increasingly prominent in the media and day to day life as a result of growing consumer awareness. This paper focuses on the impact culture has on consumers’ perceptions of the high welfare animal product market and the implications this may have for the attitude-behaviour gap. The theoretical framework combines a model which theorises that culture impacts many different aspects of an individual’s perceptions and one which argues that perceptions may impact ethical purchasing behaviour. The findings show that culture does impact consumer perceptions, and this may impact an individual’s ethical buying behaviour. Thus, managers ought to consider adaptations they can make to their marketing mixes based on the outcome of the research.